novo teste: uma parceria possível entre a Reforma Agrária e Conservação da Mata Atlântica? - Paula Ribeiro Coelho (2009)
In the 80´s, the Agrarian Reform politics started in Brazil aiming to improve lands distribution, diminishing the number of large estates. By the time lands were being occupied for Agrarian Reform, the conflict between social and environmental interests grew up. Many areas of the Brazilian Atlantic Forest that were interesting to preserve, were chosen for Agrarian Reform settlements. The conflict between conservation and agrarian politics are very intense yet in most parts of the country, especially in Amazon, were human settlements are created in areas of conserved forest, causing many negative impacts. Although, in some localities of the country, strategies to conciliate interests of settled people and environmentalists are being made. In 2002, the human settlement called Chico Mendes II was created beside the Rio Doce State Park, the most important fragment of Brazilian Atlantic Forest in the state of Minas Gerais. The park is surrounded by Eucalyptus plantation, steel industry and urban areas. Chico Mendes II settlement has the largest forest fragment outside the park boundaries (340 ha). Due to the ecological importance of the forest in the settlement, the present study aimed to stimulate environmental conservation and a better quality of life of the resident population, through the implementation of an Environmental Education program. This program started with a participatory diagnosis aiming to know the problems in the area. From the results, a visit to the park was organized, six workshops (plant and soil health, soil conservation, water conservation, Atlantic Forest biodiversity, green manure and waste disposal), a seed exchange fair and a conference organized by the park administrator. Environmental Education is a slow process and generally the results are noticed in some time. In this study, knowledge about ecosystems functions was acquired by the settlers; however, their practices are still the same as before, probably, because it takes time to change old habits, usually passed through generations. In the continuity of the research, we hope settlers incorporate other agriculture practices in their daily life, contributing to the environmental conservation.